Keragaan tiga jenis planlet anggrek Phalaenopsis asal Protocorm yang diinduksi Ethyl Methyl Sulfonate (EMS) secara in vitro - Romiyadi, Romiyadi; Komariah, Ai; Amien, Suseno (Fakultas Pertanian UNPAD, 2018)
Abstract. This research was conducted to determine the effect of concentration of Ethyl Methyl Sulfonate (EMS) to performance of three types of Phalaenopsis Planlets and to know the optimum concentration of EMS on any type of Phalaenopsis orchids. The experiment was conduc-ted at Tissue Culture Laboratory of the Faculty of Agriculture, Winaya Mukti University, Sumedang. It used a completely randomized design (CRD) with factorial pattern, that consisted of two factors and replicated twice.The first factor was the type of Phalaenopsis that resulted form hybridization which consisted of v1 (Phalaenopsis 717 X Phalae-nopsis Fire Bird), v2 (Phalaenopsis Tianong Rose X Sibling), and v3 (Phalaenopsis Luchia Pink X Phalae-nopsis Chain Xen Mammon). The second factor was the concentration of EMS that consisted of e0 (0% EMS/control), e1 (0,05% EMS), e2 (0,10% EMS), e3 (0,15% EMS), e4 (0,20% EMS), and e5 (0,25% EMS). Explant protocorm of three types of Phalae-nopsis soaked in a solution of EMS by each treat-ment for 3 hours, and cultured on MS medium Basal Modified Multiplication Shoot for 10 weeks. The experimental results showed that there are interaction between the three types of Phalae-nopsis result of a cross with a concentration of EMS to variable number of roots. Orchids P. 717 X P. Fire Bird had higherÂ number of leaves, number of roots, leaf leang, and root length than the other. The result showed that there were interaction between three species of Phalaenopsis orchid from the crossing with EMS concentration on root variables. Orchid P. 717 X P. Fire Bird has the number of leaves, the number of roots, the number of shoots, leaf length and root length better than other types. EMS concentrations independently atÂ all levels of treatment can not increase the number of leaves, the number of roots, fresh weight of planlet, leaf length, and root length.Keywords: Phalaenopsis, the concentration of EMS, in vitro cultureSari. Penelitian ini mempelajari dan mengetahui pengaruh konsentrasi Ethyl Methyl Sulfonate (EMS) terhadap keragaan planlet tiga jenis anggrek Phalaenopsis asal protocorm dan mencari konsentrasi optimum EMS untuk setiap jenis anggrek Phalae-nopsis secara in vitro.Percobaan dilaksanakan di Laboratorium Kultur Jaringan Fakultas Pertanian Universitas Winaya Mukti Sumedang. Eksperimen menggunakan Rancangan Acak Lengkap (RAL) Pola Faktorial, yang terdiri atas dua faktor dan diulang sebanyak dua kali.Faktor pertama adalah jenis anggrek Phalaenopsis hasil persilangan yang terdiri atas tiga jenis, yaitu v1 (Phalaenopsis 717 X Phalaenopsis Fire Bird), v2 (Phalaenopsis Tianong Rose X Sibling), dan v3 (Phalaenopsis Luchia Pink X Phalaenopsis Chain Xen Mammon). Faktor kedua adalah EMS yang terdiri atas enam taraf perlakuan, yaitu e0 (0% EMS/kontrol), e1 (0,05% EMS), e2 (0,10% EMS), e3 (0,15% EMS), e4 (0,20% EMS), dan e5 (0,25% EMS). Eksplan berupa protocorm dari tiga jenis anggrek Phalaenopsis hasil persilangan yang direndam dalam larutan EMS berdasarkan masing-masing perlakuan selama 3 jam, dan dikulturkan pada media MS Modified Multiplication Shoot Basal selama 10 minggu.Hasil penelitian menunjukkan terjadi interaksi antara tiga jenis anggrek Phalaenopsis hasil persilangan dengan konsentrasi EMS terhadap variabel jumlah akar.Anggrek P. 717 X P.Fire Bird memiliki jumlah daun, jumlah akar, jumlah tunas, panjang daun dan panjang akar yang lebih baik dibandingkan jenis lainnya. Konsentrasi EMS secara mandiri pada semua taraf perlakuan tidak dapat meningkatkan jumlah daun, jumlah akar, bobot segar planlet, panjang daun, dan panjang akar.Kata Kunci: Phalaenopsis, Konsentrasi EMS, dan Budidaya In Vitro